Short-term electrochemical corrosion behavior of pipeline steel in saline sandy environments. (January 2016) - He, Bin; Lu, Chun-hui; Han, Peng-ju; Bai, Xiao-hong
Abstract: In this study, we investigate the short-term electrochemical corrosion behavior of X70 pipeline steel in salinized sandy soil using the electrochemical impedance spectroscopy (EIS). The results show that the corrosion behavior of X70 steel in sandy soils with a relatively high water content ( 18%) is mainly dominated by pitting or localized corrosion, which is controlled by charge-transfer processes. The reason can be attributed to the loose corrosion products (unable to produce an effective protective layer) and discontinuous gradation in sand particles. EIS plots of X70 steel consist of two capacitive loops at the initial stage of corrosion, while a capacitive arc at high-, medium-, and low-frequency is developed after 12 h of corrosion. The capacitive loop formed at the high frequency indicates the resistance and capacitance generated by the penetration of ions into the metal surface through the sand pores and the defects of the corrosion product film. Highlights: Effect of corrosion on pipeline steel in soil environments, with a water content ( 18%) Illustration of the effect of short-term on steel corrosion behavior, using the EIS The corrosion process dominated by pitting or localized corrosion The corrosion rate of pipeline steel increased with the burial time increasing EIS plots of steel consist of two and three capacitive loops in all stages of corrosion